Simulador para el guiado de una silla de ruedas virtual en Unity 3D a través de señales EMG mediante el brazalete gForce (2021)
The adaptation of a person with reduced mobility to a wheelchair is a complex process that involves different factors, such as the state of mind, and the fact of facing the environment using an object foreign to his body, which, added to the lack of proper prior preparation can cause accidents. Despite the above and the current technological advances, there is no widely available mechanism to help a person with reduced mobility to adapt to the wheelchair he/she is going to use, and to improve the learning curve by optimizing the relationship with the environment. Considering the above, the project aims to create a virtual training system based on serious video games for rehabilitation, so that the person with reduced mobility can adapt and control in the best way the chair that later will manipulate in their daily life. This allows to obtain as a result that the person by means of a system incorporated in a myoelectric bracelet moves the chair in the direction, he/she wants starting in a virtual environment to extrapolate it later in the real environment.